2022
DOI: 10.1371/journal.pone.0268824
|View full text |Cite
|
Sign up to set email alerts
|

In their own words: An Australian community sample’s priority concerns regarding mental health in the context of COVID-19

Abstract: The COVID-19 pandemic has resulted in significant and unprecedented mental health impacts in Australia. However, there is a paucity of research directly asking Australian community members about their mental health experiences, and what they perceive to be the most important mental health issues in the context of the pandemic. This study utilises qualitative data from Alone Together, a longitudinal mixed-methods study investigating the effects of COVID-19 on mental health in an Australian community sample (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Furthermore, significant financial stress has been associated with increased interpersonal stressors, greater psychological distress and lower levels of psychological well-being (30). It is suggested that economic measures such as JobKeeper and JobSeeker (31) may have prevented the worst of the impact as government policy directed towards financial protection of Australians during COVID has been shown to improve mental health outcomes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significant financial stress has been associated with increased interpersonal stressors, greater psychological distress and lower levels of psychological well-being (30). It is suggested that economic measures such as JobKeeper and JobSeeker (31) may have prevented the worst of the impact as government policy directed towards financial protection of Australians during COVID has been shown to improve mental health outcomes (32).…”
Section: Discussionmentioning
confidence: 99%
“…To be eligible to participate, participants were required 18+, residing in Australia and have sufficient English proficiency to understand the survey and consent procedures. Further description of recruitment and consent procedures are available in Bower et al (2021Bower et al ( , 2022.…”
Section: Methods Participantsmentioning
confidence: 99%
“…State governments are responsible for determining what public health measures are appropriate and implementing them—including managing the border quarantine arrangements and the testing, tracing, and isolation regime—and managing the hospital response. States are also responsible for developing strategies to mitigate potential mental health and other effects of restrictions, and to address equity issues in the management of health outcomes and care [ 26 , 27 , 28 , 29 , 30 , 31 ]. The regulation of workplace health and safety was principally covered by state public health orders.…”
Section: A New Virus—four Roles For the National Governmentmentioning
confidence: 99%